Do Social Media Shape Gen Z’s Entrepreneurial Intention? Testing Opportunity Recognition and Self-Efficacy as Mediators - Jesselin Lim; Rakhdiny Sustaningrum (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2026)
Objective – This study examines the influence of social media usage on entrepreneurial intention of Generation Z using the mediating roles of entrepreneurial opportunity recognition and entrepreneurial self-efficacy. Design/Methodology/Approach – This study uses approach with an online questionnaire survey method involving 95 Generation Z respondents from Jakarta, Bogor, Depok, Tangerang, and Bekasi areas. The data were analyzed using Structural Equation Modeling Partial Least Square (SEM PLS) and quantitatively conducted. Findings – Social media does not directly show the willingness to start a business, but instead works effectively when it first builds the individuals' confidence in their own abilities. Implications – Social media usage primarily fosters entrepreneurial intention in Generation Z by first enhancing their self-efficacy rather than through direct influence or opportunity recognition alone. Therefore, educators and policymakers should focus on digital strategies that specifically build individual confidence and personal belief in entrepreneurial capabilities to effectively drive start-up interest. Theoretically, this research advances the literature by demonstrating that social media usage does not automatically lead to entrepreneurial intent but requires the psychological bridge of self-efficacy to be effective. Practically, it provides a roadmap for educational institutions to move beyond teaching digital literacy and instead focus on pedagogical strategies that use social media to build students' confidence and mastery in their entrepreneurial capabilities.